Implementasi Model Pembelajaran Project Based Learning Berdiferensiasi untuk Meningkatkan Kemampuan Kerja Sama Peserta Didik SMP Negeri 32 Surabaya - Suryanto, Adi; Harmanto, Harmanto; Wijayati, Nanik (CV. ULIL ALBAB CORP, 2025)
The purpose of this research is to improve the cooperation of students in grades VIII-G SMP Negeri 32 Surabaya for the 2022/2023 academic year through the implementation of the Differentiated Project Based Learning model in the subject of Pancasila and Citizenship Education. This type of research is Classroom Action Research with a total of 31 subjects. The design of this study uses a design developed by Kemmis, McTaggart and Nixon in two cycles. The data collection technique uses observation and questionnaires. The data analysis used was a quantitative percentage descriptive technique. The results of this study showed a percentage of 71.89% and cycle II showed a percentage of 87.33% and there was an increase between cycle I and cycle II of 15.44%. Based on the results of the study, it can be concluded that the differentiated project-based learning model is able to improve the cooperative ability of students in class VIII-G SMP Negeri 32 Surabaya.